Starch digestibility and apparent metabolizable energy of western Canadian wheat market classes in broiler chickens. (11th July 2018) - Karunaratne, N D; Abbott, D A; Hucl, P J; Chibbar, R N; Pozniak, C J; Classen, H L
Abstract: Wheat is the primary grain fed to poultry in western Canada, but its nutritional quality, including the nature of its starch digestibility, may be affected by wheat market class. The objectives of this study were to determine the rate and extent of starch digestibility of wheat market classes in broiler chickens, and to determine the relationship between starch digestibility and wheat apparent metabolizable energy (AME). In vitro starch digestion was assessed using gastric and small intestinal phases mimicking the chicken digestive tract, while in vivo evaluation used 468 male broiler chickens randomly assigned to dietary treatments from 0 to 21 d of age. The study evaluated 2 wheat cultivars from each of 6 western Canadian wheat classes: Canadian Prairie Spring (CPS), Canadian Western Amber Durum (CWAD), CW General Purpose (CWGP), CW Hard White Spring (CWHWS), CW Red Spring (CWRS), and CW Soft White Spring (CWSWS). All samples were analyzed for relevant grain characteristics. Data were analyzed as a randomized complete block design and cultivars were nested within market class. Pearson correlation was used to determine relationships between measured characteristics. Significance level was P ≤ 0.05. The starch digestibility range and wheat class rankings were: proximal jejunum – 23.7 to 50.6% (CWHWS c, CPS bc, CWSWS bc, CWRS ab, CWGP a, CWAD a ); distal jejunum – 63.5 to 76.4% (CWHWS c, CPS bc, CWSWS bc, CWRS ab, CWGP a, CWAD a ); proximal ileum – 88.7 to 96.9% (CWSWS c, CPS bc, CWHWS bc, CWRS b, CWGP b, CWAD a ); distal ileum – 94.4 to 98.5% (CWSWS b, CWHWS b, CPS b, CWRS ab, CWGP ab, CWAD a ); excreta – 98.4 to 99.3% (CPS b, CWRS b, CWHWS b, CWSWS ab, CWGP ab, CWAD a ). Wheat class affected wheat AMEn with levels ranging from 3, 203 to 3, 411 kcal/kg at 90% DM (CWRS c, CWSWS c, CPS b, CWGP b, CWAD a, CWHWS a ). Significant and moderately strong positive correlations were observed between in vitro and in vivo starch digestibility, but no correlations were found between AME and starch digestibility. In conclusion, rate and extent of starch digestibility and AME were affected by western Canadian wheat class, but starch digestibility did not predict AME.